Progression to lung fibrosis in severe COVID-19 patients: A morphological and transcriptomic study in postmortem samples - Pérez-Mies, Belén; Caniego-Casas, Tamara; Bardi, Tommaso; Carretero-Barrio, Irene; Benito, Amparo; García-Cosío, Mónica; González-García, Irene; Pizarro, David; Rosas, Marta; Cristóbal, Eva; Ruano, Yolanda; Garrido, María Concepción; et al. (Frontiers in Medicine, 2022)
The development of lung fibrosis is a major concern in patients recovered from severe COVID-19 pneumonia. This study aimed to document the evolution of diffuse alveolar damage (DAD) to the fibrosing pattern and define the transcriptional programs involved. Morphological, immunohistochemical and transcriptional analysis were performed in lung samples obtained from autopsy of 33 severe COVID-19 patients (median illness duration: 36 days). Normal lung and idiopathic pulmonary fibrosis (IPF) were used for comparison. Twenty-seven patients with DAD and disease evolution of more than two weeks had fibrosis. Pathways and genes related with collagen biosynthesis and extracellular matrix biosynthesis and degradation, myofibroblastic differentiation and epithelial to mesenchymal transition (EMT) were overexpressed in COVID-19. This pattern had similarities with that observed in IPF. By immunohistochemistry, pathological fibroblasts, with CTHRC1 and SPARC expression, increased in areas of proliferative DAD and decreased in areas of mature fibrosis. Immunohistochemical analysis demonstrated constitutive expression of cadherin-11 in normal epithelial cells and a similar pattern of cadherin and catenin expression in epithelial cells from both normal and COVID-19 samples. Transcriptomic analysis revealed downregulation of the Hippo pathway, concordant with the observation of YAP overexpression in hyperplastic alveolar epithelial cells. Progression to fibrosis in severe COVID-19 is associated with overexpression of fibrogenic pathways and increased in CTHRC1- and SPARC-positive pathological fibroblasts. Whereas the Hippo pathway seemed to be implicated in the response to epithelial cell damage, EMT was not a major process implicated in COVID-19 mediated lung fibrosis.